Distribusi Serapan Sayur Paprika pada Rantai Pasok di Kecamatan Baturiti - Dewi, I Gusti Ayu Indah Kusuma; Aviantara, I Gusti Ngurah Apriadi; Widia, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 8 No 1 (2020): April, 2019)
This study aimed to determine the marketing distribution channel to analyze the absorption of paprika from the farmer in Baturiti district to the last costumers to calculate the marketing margins obtained in each distribution channel. This research was conducted in July-August 2018. This study used purposive sampling survey. There are five distribution channels of paprika from the farmer in Baturiti regency to the last costumers namely: 1 st line (Farmer ? Traditional Market Trader ? costumers), 2 nd line  (Farmer ? Local Collector ? City Collector? Consumer), 3 rd   line  (Farmer ? Local Collector ? City Collector? Costumer), 4 th line (Farmer ? City Collector? Consumer), 5 th line (Farmer ? City Collector? Consumer). The distribution shows that the rate market of paprika and farmer produce 2.655 monthly. Absorption of paprika rate that is distributed by farmer  to local collector, city collector, and traditional market are 25,6 percent, 38,8 percent, 35,6 percent. Paprika  that is distributed by local collector to city collector and traditional market are 19,6 percent them 6 percent. City collector obtain 58,4 percent paprika from farmer and local collector then later distribute 29,8 percent, 21,5 percent, 7,1 percent the paprika to each hotel or restaurant, supermarket, and traditional market. City collect obtain 58,4 percent paprika for faram and local collect then later distribution the to hotel or restaurant, supermarket and traditional market by the percentage of 29,8 percent, 21,5 percent, 7,1 percent respectively. Based on the five lanes determined in this study, lane III is the longest distribution, but the lane has the highest marketing margin and profit margin, lane III and V. Line I is the shortest distribution path of the five lanes, and has a marketing margin and lowest profit because the marketing costs incurred are small and the selling price at the final consumer level is also the lowest among the other five lines.